ANALYTICAL TYPOLOGY OF HISTORICAL MOSQUES IN WEST AZERBAIJAN PROVINCE - Nadereh Shojadel (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
West Azerbaijan Province located in the most northwestern part of Iran, with historical richness and old civilization, and ethnic-religious diversity, encompasses various historical temples such as mosque (Masjid), church, and synagogue. This study aims at analyzing the typology of historical mosques of the province. To this end, by identifying and analyzing 20 cases of historical mosques of West Azerbaijan Province, the characteristics of the mosques and their typology of them are introduced and analyzed. The study tends to answer two questions: what spaces the mosques of West Azerbaijan include, and what are their physical characteristics? What are the types of West Azerbaijan mosques? The previous studies and primary analysis of the samples can assume that the pattern of historical mosques of West Azerbaijan Province is a pattern different from historical mosques of Central Plateau of Iran. The purpose of this study is the recognition of case samples and their typology due to architectural spaces and their physical characteristics and introducing the dominant type. The method in this study is descriptive-analytical research. Besides, to evaluate the conceptual framework of the research and to identify the research literature, documentary, and library method is used. Also, a survey is done using field methods for the identification and documentation of studied mosques. According to the results obtained from this study, the columnar nave (Shabistan) is the main space of mosques and is observed in 16 samples in this study. After that, the domed square (Gonbadkhaneh) is the space, which was present in 5 cases of studied samples. Hence, studied historical mosques are divided into two main types of columnar nave mosques and domed square mosques. Each type includes other subsets, which have been divided due to other characteristics, such as the existence or inexistence of courtyard, and type of nave covering. Finally, it could be mentioned that both nave and domes square types have closed volumes, and the majority of them lack courtyard.